Integration of Mercosur in the global economy - Andreas Baur; Lisandra Flach; Feodora Teti (CESifo GmbH, 2023)
More than twenty years after the beginning of negotiations, a new window of opportunity seems to have opened for the ratification of a trade agreement between the European Union and Mercosur. For Mercosur, this comes at a crucial juncture in its integration process: the future of the South American trade bloc appears to be more uncertain than ever, with member states holding diverging views on Mercosur's objectives. Thirty years after its foundation, the original goals of Mercosur's integration process have been only partially achieved. While there has been some success in terms of trade liberalization within Mercosur, the goals of forming a customs union and pursuing deeper integration steps remain unfulfilled. High Most Favored Nation (MFN) tariffs and non-tariff trade barriers within the region, coupled with the lack of trade agreements, hinder the integration of Mercosur countries into the global economy. In this report, we take the perspective of Mercosur member states. We describe the evolution of trade flows, highlighting China's growing importance and Europe's declining importance as a trading partner. Next, we analyze trade policy developments within the region and the integration of member states into regional and global value chains. Finally, we emphasize the importance of the EU-Mercosur trade agreement.
Keywords: 330